The Application Of Deep Learning In Islamic Religious Education In The Digital Age In The 10th Grade At Jumapolo State High School - Asma Nurul Azizah; Dartim Dartim (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
The digital age has brought significant transformation to education, requiring learning in Islamic Religious Education to move beyond rote memorization toward deeper understanding and active participation. This study analyzes the implementation of a deep learning approach in Islamic Religious Education among 10th-grade students at Jumapolo State High School in the digital age. A qualitative descriptive method was employed, involving Islamic Religious Education teachers as interview informants and 10th-grade students as questionnaire respondents. Data were collected through in-depth interviews and Google Forms-based questionnaires. The data analysis process included data reduction, data presentation, and conclusion drawing. The findings revealed that Problem-Based Learning (PBL) and Project-Based Learning (PjBL) models were applied to facilitate deep learning in Islamic Religious Education. These models encourage students to engage with learning materials and connect them to real-life situations, resulting in positive learning experiences characterized by interest and self-directed learning. The learning process contributes to students’ cognitive, affective, and psychomotor development. While the use of digital technology, including artificial intelligence (AI), helps students access various information sources, it also presents challenges, as students tend to rely on AI without always verifying the accuracy of the information. Therefore, teacher guidance and strengthened digital literacy are essential. Overall, the implementation of deep learning in the digital era offers opportunities to improve the quality of Islamic religious education.